2001
DOI: 10.1103/physrevlett.87.147201
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transition and Pair Formation inFe3O2BO3

Abstract: We observe for the first time a structural phase transition in the oxyborate Fe3O2BO3 which occurs along three leg ladders present in this material. X-ray diffraction shows that this transition at 283 K is associated with a new phase where atomic displacements occur in alternate directions perpendicular to the axis and within the plane of the ladders. Magnetic data show that these displacements lead to the formation of singlet pairs which dissociate close to the structural transition. Anomalies in the transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 8 publications
7
85
1
2
Order By: Relevance
“…The temperature dependence of this coercive field enters via the dependence of the wall energy on the anisotropy constant K 1 , γ ∝ √ AK 1 , where A is proportional to the exchange coupling. 25 For comparison, at the same temperature T = 10 K, and θ H = 0 one obtains H b C M r = γ /l = 8.73×10 6 BO 3 , but not enough to explain the observed increase, and K 1 may be similar in both compounds, it can be concluded that the main reason for the increase in coercivity field is the increase of the number of defects in the crystal upon the introduction of Fe, which in turn reduces strongly the average distance between defects, l.…”
Section: Magnetic Hysteresismentioning
confidence: 98%
See 3 more Smart Citations
“…The temperature dependence of this coercive field enters via the dependence of the wall energy on the anisotropy constant K 1 , γ ∝ √ AK 1 , where A is proportional to the exchange coupling. 25 For comparison, at the same temperature T = 10 K, and θ H = 0 one obtains H b C M r = γ /l = 8.73×10 6 BO 3 , but not enough to explain the observed increase, and K 1 may be similar in both compounds, it can be concluded that the main reason for the increase in coercivity field is the increase of the number of defects in the crystal upon the introduction of Fe, which in turn reduces strongly the average distance between defects, l.…”
Section: Magnetic Hysteresismentioning
confidence: 98%
“…6,7 Short and long Fe-Fe bonds are formed in the 4-2-4 triads in the direction perpendicular to the axis of the ladder, with a doubling of the cell parameter on the c axis that affects the magnetic properties of the material. In this work the magnetic properties of the substitutional compound Co 2.25 Fe 0.75 O 2 BO 3 are studied and compared to those of the parent compounds Co 3 O 2 BO 3 and Fe 3 O 2 BO 3 -the two homometallic oxyborates with ludwigite structure available now.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The structural transition at T S Ϸ 283 K is accompanied by a change in the activation energy of the electrical resistivity. 1 An important distinction between the Fe 3 O 2 BO 3 ludwigite and the common Peierls systems is the existence of local moments belonging to the Fe ions which interact with the CDW; besides, the mechanism responsible for the CDW formation is different from that of the Peierls distortion in onedimensional metals. 2 Here we are dealing with an excitonic instability due to the coupling between an empty band and a fully occupied one.…”
Section: Introductionmentioning
confidence: 99%